2014
DOI: 10.1210/en.2014-1182
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Corticotropin-Releasing Factor Neurons by Fluorescent Proteins in the Mouse Brain and Characterization of Labeled Neurons in the Paraventricular Nucleus of the Hypothalamus

Abstract: Corticotropin-releasing factor (CRF) is the key regulator of the hypothalamic-pituitary-adrenal axis. CRF neurons cannot be distinguished morphologically from other neuroendocrine neurons in the paraventricular nucleus of the hypothalamus (PVH) without immunostaining. Thus, we generated a knock-in mouse that expresses modified yellow fluorescent protein (Venus) in CRF neurons (CRF-Venus), and yet its expression is driven by the CRF promoter and responds to changes in the interior milieu. In CRF-Venus, Venus-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 31 publications
4
63
0
Order By: Relevance
“…Notably, retrogradely‐labeled CRH + cells tended to reside in the posterior BLA, as 40% of all CRH‐expressing cells in this region projected to the NAc. Notably, both CRH (Itoi et al, ) and CRH mRNA (Kono et al, ) have been observed in mice and specifically in transgenic mice (CRH‐Cre and a Venus reporter), using tools that are completely independent from those employed here.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, retrogradely‐labeled CRH + cells tended to reside in the posterior BLA, as 40% of all CRH‐expressing cells in this region projected to the NAc. Notably, both CRH (Itoi et al, ) and CRH mRNA (Kono et al, ) have been observed in mice and specifically in transgenic mice (CRH‐Cre and a Venus reporter), using tools that are completely independent from those employed here.…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of new tools that enable specific activation of identified cell populations will be extremely beneficial for gain ing a better understanding of the interactions between cotransmitters in the PVN. In this vein, recent studies have described new mouse models that allow for both the identification and the genetic targeting of specific subsets of PNCs 99,113,114 . One important limitation that must be addressed is the dearth of information about the activity of PNCs and CRHproducing neurons in vivo, particularly in response to stress exposure; developing and implementing approaches that allow for the use of electrophysiology and/or imaging techniques in awake, behaving animals will be a considerable advance in help ing to make causal links between changes in synaptic function or plasticity and the output of stress circuitry.…”
Section: Box 1 | Plasticity Metaplasticity and Kairoplasticitymentioning
confidence: 99%
“…Visualizing CRH-expressing neurons through immunohistochemical analysis is difficult without prior administration of compounds that inhibit axonal transport to promote the somatic accumulation of neuropeptides [4]. In transgenic mice, PVN-CRH neurons can be tagged by specifically expressing green fluorescent protein driven by the endogenous Crh promoter [5-7]. However, many studies use established rat stress models to study HPA axis activity.…”
Section: Introductionmentioning
confidence: 99%